2008
DOI: 10.1143/jjap.47.2016
|View full text |Cite
|
Sign up to set email alerts
|

Field Emission from Conducting Polymer/Single-Walled Carbon Nanotube Composite Prepared by AC Coupled Electrophoresis

Abstract: The field emission properties of a carboxylic-acid-terminated single-walled carbon nanotube (SWNT-COOH)/conducting polymer [poly(3-octylthiophene), P3OT] composite film prepared by ac-coupled electrophoresis have been investigated. It was found that positively charged SWNT-COOH/P3OT colloids were selectively deposited onto an indium tin oxide (ITO) electrode, and the spatial resolution of about 1 mm was successfully obtained when ITO was coated selectively with partially fluorinated polyimide (FPI). The field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The PANI nanofibers have diameter in the range of 50-150 nm and length in several microns. 32 The FTIR analysis of synthesized product also confirms the formation of doped PANI, supporting the Uv-visible results. Typical TEM images shown in Figs.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The PANI nanofibers have diameter in the range of 50-150 nm and length in several microns. 32 The FTIR analysis of synthesized product also confirms the formation of doped PANI, supporting the Uv-visible results. Typical TEM images shown in Figs.…”
Section: Resultssupporting
confidence: 74%
“…1, clearly shows the formation of PANI nanofibers under the prevailing experimental conditions. 15,32 A set of characteristic peaks at 310 nm (due to -* transition), 410 nm (due to polaron-* transition) and a broad hump around 800-850 nm (due to -polaron transition) indicates the formation doped PANI phase. In order to check whether the nanofibers are 'tubular' or not, TEM analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency behavior of specific admittance of 0.05 vol% of CNTs-filled polyimides composites determined that its conductivity properties follow a percolation-like power law, with a comparatively low percolation threshold (Tzeng et al 2008;Guo et al 2009;Zha et al 2013). The measurement of the current-voltage demonstrated that the composites displayed a nonohmic behavior, representing a quantum tunneling conduction procedure (Itoh et al 2008). Thus, it is concluded that the conductivity of the composites results from the formation of conducting pathways to the polyimides by CNTs (Bong et al 2006;Yang et al 2007;Kim et al 2007;Li and Bai 2011).…”
Section: Cnts: In Polyimides Polymeric Compositesmentioning
confidence: 99%
“…2,3) On the other hand, carbon nanotubes (CNTs) have attracted significant attention in electronics owing to their excellent thermal and chemical stabilities, very high thermal and electrical conductivities, and very high aspect ratio, which is suitable for electrode materials and field emitters of electrons, and so on. [4][5][6][7][8] The incorporation of CNTs into polymer matrices has been shown to markedly improve the mechanical strength and electrical and thermal conductivities of the resulting composites. 9,10) A variety of nanomaterials for conductive fillers, such as a metal-based composite, nanographene, and a CNT/polymer composite have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a previous study, we investigated the field-emission (FE) properties of a poly(3-octylthiophene)/ SWCNT-COOH composite deposited by ac-coupled electrophoresis and determined that it is an easy and extremely lowcost fabrication technique. 8) A low turn-on electric field for FE has been expected in polymer/SWCNT composites because of the very high field-enhancement factor of >1000 at the edge of SWCNTs that arises from their very high aspect ratio. The FE properties were markedly improved when the composites were embedded into a micropatterned electrode because of the vertical alignment of CNTs along the micropatterned polymer banks.…”
Section: Introductionmentioning
confidence: 99%